SAT0141 Changes of Bone Density and Microarchitecture in Rheumatoid Arthritis Patients with Early Disease: A One-Year Study with HR-PQCT. (15th July 2016) - Wong, P.C.; Zhu, Y.; Qin, L.; Tam, L.-S.
Abstract : Background: Periarticular and systemic osteoporosis is a major feature in patients with rheumatoid arthritis (RA). Bone loss in RA is considered to be a result of chronic inflammation, particularly at the early stage of the disease. High Resolution peripheral Quantitative Computed Tomography (HR-pQCT) is an in vivo 3D imaging modality dedicated to peripheral skeleton imaging. Whether a better controlling of the disease inflammation could lead to a preservation of vBMD and microarchitecture is to be determined. Objectives: This one-year cohort study in RA patients with early disease (onset <2 years) aimed to compare changes of vBMD and bone microarchitecture indices at the distal radius and tibia between patients who achieved and those who did not achieve disease remission. Methods: Forty-seven RA patients (age: 54.5±11.8 years) with disease onset <2 years and with active disease (Disease Activity Score in 28 joints [DAS28] ≥3.2) were recruited for this one-year study. Disease remission at 12 months was assessed as Simplified Disease Activity Score ≤3.3. HR-pQCT imaging of the distal radius and tibia was performed at baseline and 12 months. Results: At 12 months, 20 patients achieved disease remission and 27 patients remained with activity disease. There was no significant difference in baseline DAS28 score (4.93 vs. 4.92, p>0.05) and age between the two groups. In patients who did not achieve disease remission, particularly at the distal radius, there were decreases in cortical and trabecular vBMD, cortical thickness and trabecular number, and increase in trabecular separation (Table 1 ). Increase in cortical porosity presented as the most prominent deterioration of bone microarchitecture (20%). Only changes in trabecular separation (2.87%) and cortical vBMD (-1.12%) achieve statistical significance. In patients who achieve disease remission, decrease in vBMD and deterioration in bone microarchitecture were in general to a lesser extent than their counterparts. In particular, there appeared to be a decrease in cortical porosity in these patients (-6.62%). However, there was no significant group-wise difference in changes of vBMD and microarchitectural indices (all p>0.05). Conclusions: There was a trend towards a preservation of vBMD and bone microarchitecture in RA patients who achieve disease remission. An early and better control of disease activity might reduce the future risk of osteoporosis in RA patients. Disclosure of Interest: None declared